When minoritized languages encounter MT - Nora Aranberri; Uxoa Iñurrieta (JoSTrans: The Journal of Specialised Translation, 2024)
Machine translation (MT) is improving even for low-resource minoritized languages such as Basque, for which free online engines are available. However, the level of adoption and common practices involving the technology are unknown, even though it has the potential to disrupt a carefully planned Basque language revitalization and sustainability process. To shed light on MT usage habits and perceptions among the Basque community, we report on the results of a survey of language specialists and general users, and a focus group with professional translators and interpreters. The data shows that MT is already becoming more popular among users of all backgrounds and that, overall, the attitude towards the technology is positive, which might result in increased use in the future. However, participants express concern about the impact MT will have on the development of Basque. The results call for further research on the language impact of MT and MT literacy initiatives.